Bilateral chylothorax following total thyroidectomy with neck lymph node dissection for thyroid cancer: a case report and literature review - Wang, Yunsheng; Liu, Xudong; Wang, Xingyue; Tian, Youxin; Liu, Qinjiang; Wang, Jun; Xue, Jincai (Frontiers in Oncology, 2025)
PurposeInvestigating the diagnosis and treatment of bilateral Chylothorax after neck lymph node dissection for thyroid cancer.MethodsThe clinical data of a patient with bilateral chylothorax after neck lymph node dissection for thyroid cancer were retrospectively analyzed, and the relevant literature was reviewed.ResultsThe patient underwent a total thyroidectomy and left neck lymph node dissection, with no evidence of lymph fluid leakage observed during the operation. The patient experienced chest tightness, shortness of breath, dyspnea, and decreased lung auscultation breath sounds on the 7th day after the surgery. The chest X-ray examination revealed the presence of bilateral pleural effusion. Under ultrasound guidance, bilateral thoracic closed drainage tube was implanted, and a small sample of the milky white fluid was tested for chylothorax, yielded positive results. The patient is diagnosed with bilateral chylothorax. After received conservative treatment, the patient’s drainage flow gradually decreased. Subsequent review of a chest X-ray showed no signs of chest hydrops, and as a result, the thoracic drainage tube was removed. The patient eventually recovered and was subsequently discharged.ConclusionBilateral chylothorax is a rare complication following neck lymph node dissection for thyroid cancer. It is deemed safe and effective to administer active conservative treatment upon early detection.